10% increase in oil production through a field applied APC in a Petrobras ultra-deepwater well. (October 2019) - Diehl, Fabio C.; Machado, Tatiane O.; Anzai, Thiago K.; Almeida, Cristina S.; Moreira, Cristiano A.; Nery Jr, Gesner A.; Campos, Mario C.M.M.; Farenzena, Marcelo; Trierweiler, Jorge O.
Abstract: As an offshore oil well ages, it is common for the production system to face multiphase flow problems such as limit cycles. This phenomenon, known as slugging in the jargon of the oil industry, causes oscillations in the well's flowrate and pressure. Its main effects are reducing production and increasing the risk of operational discontinuity due to shut down. In this paper, an advanced control process (APC) strategy is presented to deal with the slugging problem in oil wells. The strategy uses a two-layer coupled control structure: a regulatory via a PID control, and a supervisory via a model-based predictive control (MPC). The structure proposed was applied to a real ultra-deepwater well in Petrobras that was partially restricted by the choke valve to avoid the propagation of oscillatory behavior to the production system. As a result, the well has achieved a 10% oil production increase while maintaining the flow free of severe slugging, which meant an increment of about 240 barrels a day for that specific well.